Bride - Hazelwood, Ali (Berkley, 2024)
Misery Lark, daughter of the most powerful Vampyre councilman of the Southwest must leave her life of anonymity among the humans and uphold a historic alliance with the Weres by marrying their Alpha, Lowe Moreland.